2021
DOI: 10.1080/2162402x.2021.1956143
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of arginase modulates T-cell response in the tumor microenvironment of lung carcinoma

Abstract: Immunotherapy has demonstrated significant activity in a broad range of cancer types, but still the majority of patients receiving it do not maintain durable therapeutic responses. Amino acid metabolism has been proposed to be involved in the regulation of immune response. Here, we investigated in detail the role of arginase 1 (Arg1) in the modulation of antitumor immune response against poorly immunogenic Lewis lung carcinoma. We observed that tumor progression is associated with an incremental increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 63 publications
2
37
0
Order By: Relevance
“…5a). Both arginase inhibitor (ARGi, OAT-1746, a membrane-permeable, potent inhibitor of both arginase isoforms [22][23][24] ) and ROS inhibitor (ROSi, N-acetylcysteine) nearly completely restored the proliferation of T-cells that was inhibited by co-culture with CECs isolated from NHA mice (Fig. 5b), similar to CECs isolated from neonates (Supplementary Fig.…”
Section: Cecs Degrade L-arg and Produce Ros Leading To The Suppression Of T-cellssupporting
confidence: 53%
“…5a). Both arginase inhibitor (ARGi, OAT-1746, a membrane-permeable, potent inhibitor of both arginase isoforms [22][23][24] ) and ROS inhibitor (ROSi, N-acetylcysteine) nearly completely restored the proliferation of T-cells that was inhibited by co-culture with CECs isolated from NHA mice (Fig. 5b), similar to CECs isolated from neonates (Supplementary Fig.…”
Section: Cecs Degrade L-arg and Produce Ros Leading To The Suppression Of T-cellssupporting
confidence: 53%
“…In our model, Rab27a −/− CML did not significantly influence other immunosuppressive cells, such as Bregs or myeloid suppressive cells (supplemental Figure 8A-D), which additionally exhibited low abundance, compared with mouse models of solid tumors. 35,36 This implicated direct modulation of Tregs by Rab27a-dependent leukemic EVs rather than indirectly via B cell-T-cell, or macrophage-T cell interactions.…”
Section: Resultsmentioning
confidence: 99%
“…As the previous studies found, the metabolites of tryptophan metabolism supported tumor-associated macrophages to facilitate immunosuppression in pancreatic cancer [ 19 ]. High levels of arginase that catalyze the L-arginine can inhibit the proliferation of antigen-specific T cells in lung cancer [ 20 ]. Besides, serine and glycine metabolism can destroy the anticancer function of macrophages and neutrophils [ 21 ].…”
Section: Discussionmentioning
confidence: 99%